LOYALTY AND PATHOS IN ZULFIYA’S WORK - Shavkatova Jasmina (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article, the life and work of Zulfia Israilova, a unique woman, a great mother, a symbol of loyalty and devotion, is covered.It should be added that Zulfia was a woman who had a keen sense of the common human heart – a hardworking woman who valiantly fought for the equal rights of Eastern women in society.